STRATEGI PENGEMBANGAN USAHA ABON DAGING SAPI PADA INDUSTRI âCITRA LESTARI PRODUCTIONâDI KOTA PALU - Putri, Trimiranti; Lamusa, Arifuddin (AGROTEKBIS, 2017)
Abon are foods made from meat that has been shredded or separated fiber, then add seasonings and fried. The purpose of the SME